Study of Ho-doped Bi2Te3 topological insulator thin films - Harrison, SE; Collins-McIntyre, LJ; Zhang, SL; Baker, AA; Figueroa, AI; Kellock, AJ; Pushp, A; Chen, YL; Parkin, SSP; Harris, JS; van der Laan, G; Hesjedal, T (American Institute of Physics, 2015)
Breaking time-reversal symmetry through magnetic doping of topological insulators has been identified as a key strategy for unlocking exotic physical states. Here, we report the growth of Bi2Te3 thin films doped with the highest magnetic moment element Ho. Diffraction studies demonstrate high quality films for up to 21% Ho incorporation. Superconducting quantum interference device magnetometry reveals paramagnetism down to 2 K with an effective magnetic moment of ∼5 μB/Ho. Angle-resolved photoemission spectroscopy shows that the topological surface state remains intact with Ho doping, consistent with the material's paramagnetic state. The large saturation moment achieved makes these films useful for incorporation into heterostructures, whereby magnetic order can be introduced via interfacial coupling.